Transforming health care systems towards high-performance organizations: qualitative study based on learning from COVID-19 pandemic in the Basque Country (Spain) - Ane Fullaondo; Irati Erreguerena; Esteban de Manuel Keenoy (BMC, 2024)
Abstract Background The COVID-19 pandemic is one of the worst health catastrophes of the last century, which caused severe economic, political, and social consequences worldwide. Despite these devastating consequences, lessons learned provide a great opportunity that can drive the reform of health systems to become high-performing, effective, equitable, accessible, and sustainable organisations. This work identifies areas in which changes must be encouraged that will enable health systems to deal effectively with current and future challenges, beyond COVID-19. Methods A realist design was chosen, based on qualitative data collection techniques, content analysis and triangulation to identify key domains of organizational interventions behind the changes implemented to react to the COVID-19 pandemic in the Basque Country. Twenty key informants were used as an expert source of information. Thematic analysis was done using the Framework Method. Results The analysis of the interviews resulted in the identification of 116 codes, which were reviewed and agreed upon by the researchers. Following the process of methodological analysis, these codes were grouped into domains: seven themes and 23 sub-themes. Specifically, the themes are: responsiveness, telehealth, integration, knowledge management, professional roles, digitisation, and organisational communication. The detailed description of each theme and subtheme is presented. Conclusions The findings of this work pretend to guide the transformation of health systems into organisations that can improve the health of their populations and provide high quality care. Such a multidimensional and comprehensive reform encompasses both strategic and operational actions in diverse areas and requires a broad and sustained political, technical, and financial commitment.